Outcomes of patients with detectable CMV DNA at randomization in the phase III trial of letermovir for the prevention of CMV infection in allogeneic hematopoietic cell transplantation. Issue 6 (18th January 2020) - Marty, Francisco M.; Ljungman, Per T.; Chemaly, Roy F.; Wan, Hong; Teal, Valerie L.; Butterton, Joan R.; Yeh, Wendy W.; Leavitt, Randi Y.; Badshah, Cyrus S.
Abstract : Letermovir, a cytomegalovirus (CMV) terminase‐complex inhibitor, is indicated for prophylaxis of CMV infection and disease in adult CMV‐seropositive recipients of allogeneic hematopoietic cell transplantation (HCT). In a phase III, double‐blind, randomized trial, letermovir significantly reduced the risk of clinically significant CMV infection (CS‐CMVi) vs placebo through Week 24 post‐HCT. This analysis investigated outcomes in participants with detectable CMV DNA at randomization, who were excluded from the primary efficacy analysis. In total, 70 of 565 randomized participants had detectable CMV DNA at randomization (letermovir 48; placebo 22). Study treatment completion rates were greater in letermovir‐treated participants compared with placebo (52.1% vs 9.1%). The incidence of CS‐CMVi or imputed primary endpoint events through Week 24 were 64.6% and 90.9% in the letermovir and placebo groups, respectively (treatment difference −26.1%; P  = .010). Kaplan‐Meier event rates for CS‐CMVi onset through Week 14 (end‐of‐treatment period) were 33.1% for letermovir and 86.6% for placebo ( P  < .001). Median viral loads at the CS‐CMVi events was similar in both treatment arms. All‐cause mortality through Week 24 posttransplant was 15.0% for letermovir and 18.2% for placebo; through Week 48, mortality rates were 26.5% and 40.9%, respectively ( P  = .268). Overall, clinical outcomes were similar to those reported for participants with undetectable CMV DNA at randomization. Abstract : Among 70 patients who had detectable cytomegalovirus DNA at the time of randomization and were not part of the primary efficacy analysis population of the phase 3 letermovir prophylaxis trial in hematopoietic cell transplantation, 33.1% of letermovir‐treated patients developed cytomegalovirus disease or DNAemia requiring preemptive treatment compared to 86.6% patients who received placebo by end of the prophylaxis period.